A Relationship Between Contraception Service Sources And Modern Contraception Methods Used By Couple Of Bearing Age In Indonesia - Dyah Pradnya Paramitha; Ratih Devi Alfiana; Lia Dian Ayuningrum; Fatimasari Fatimasari (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2020)
Population growth is a big problem for a country. The number of couples of childbearing age who using contraception should be increased in order to deal with this problem. Based on the results of the 2017 Indonesian Health Demographic Survey (SDKI), the number of couples of childbearing age using contraceptives was 57%. To increase the use of contraception, it is necessary for health facilities to play a role not only as providers of contraception, but also as providers of promotive and preventive services, so that couples of childbearing age can rationally choose the contraception to be used as needed. This research aimed to discover the relationship between contraceptive service sources and the modern contraceptive method used by couples of childbearing age. This research used the secondary data from the 2018 Program Performance and Accountability Survey of Population, Family Planning, and Family Development (abbreviated SKAP-KKBPK in Indonesia), using the cross-sectional research design and the Chi-square bivariate analysis. The population used in this research was all couples of childbearing age in Indonesia who becomes responden in SKAP-KKBPK, which were 60.599 couples, and the samples were all couples of childbearing age who used modern contraception, which were 26,776 couples. The research known that as much as 76,9 % couple of childbearing chose to use short-term contraceptive methods and 76,51 % choose visit to a source of private service contraceptive to get those contraceptives. Couples of childbearing age who use short-term contraceptive visit to private service contraceptive (85.9 %) and couples of childbearing age who use long term contraceptive visit to government service contraceptive (52.6 %). The conclusion of this research is the relationship between source service contraception with modern contraception method used. The source service contraceptive must to offer the quality service to encourage.So that couples of childbearing age can rationally choose the contraception to be used as needed.